Conception and Implementation of One Day One Verse at PMI Dea Malela - Salahudin Salahudin; Muh. Nur Rochim Maksum; Nourelhuda S. B. Elmanaya; Mohamed Gamal Ibrahim ElBasiouny (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
Al-Qur'an in the view of Muslims, is a way of life. Verse after verse has a very deep meaning and content beyond the famous poets though. Thus, Muslims need to understand the contents of the Qur'an so that they can be contemplated and practised. One Day One Verse (ODOV) has an important role in increasing the understanding of students at Dea Malela Modern International Islamic Boarding School. One Day One Verse is one of PMI Dea Malela's flagship programs because it is quite different from other programs such as the tahfidz program and the like. The purpose is that students (male and female) can memorize, understand, recite, and apply One Day One Verse. The research method presented is a case study method combined with various related references. Thus, this research includes descriptive research, which focuses on a systematic explanation of the facts obtained when it was conducted. The research subjects were students by conducting interviews and direct observation of activities. The results showed that PMI Dea Malela’s students strongly supported this activity because they felt it had a positive impact on their understanding of the al-Qur’an. Applicatively, some of the verses that have been memorized have been practised in everyday life.